A Few Bivalent metal Complexes with 2-Acetyl Thiophen Thiosemicarbazone - Ranjan Jha, Raj; Ram Sahu, Sita (Asian Journal of Chemistry, 2010)
Metal complexes of the type [MLX2] [where M = Co(II), Ni(ll)and Cu(II), L = 2-acetyl thiophene tbiosemicarbazone (ATTS),(X = Cl-, Br-, NO3- and CIO4-) have been synthesised in neutralmedium and characterised. The IR spectrum of the complexes suggestthe coordination of the metal ion to the ligand throughazomethine nitrogen, tbiol-sulphur and sulphur atom of cyclicthioether. The ligand acts as a bi-bidentate chelating agent resultingin polymeric structure of the complexes. The octahedral geometryof the complexes has been proposed on the basis of elementalanalysis, magnetic susceptibility measurements and spectral studies.Fungicidal screening of the complexes shows them active againstAspergillus niger, Fusarium oxysporium and Helminthosporiumoryzae.